2008
DOI: 10.1373/clinchem.2008.107722
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Pompe Disease by Measuring Acid α-Glucosidase Activity Using Tandem Mass Spectrometry

Abstract: background: Pompe disease, caused by the deficiency of acid α-glucosidase (GAA), is a lysosomal storage disorder that manifests itself in its most severe form within the first months of life. Early detection by newborn screening is warranted, since prompt initiation of enzyme replacement therapy may improve morbidity and mortality. We evaluated a tandem mass spectrometry (MS/MS) method to measure GAA activity for newborn screening for Pompe disease. methods: We incubated 3.2-mm punches from drie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 13 publications
2
50
0
Order By: Relevance
“…Assuming all four patients were affected, a frequency of 1:2,570 can be derived. In our study, we found similar mean enzyme activity and standard deviation in whole sample cohort as was found in the Austrian study (Dajnoki et al 2008). However, applying a cutoff value of 2 mmol/l/h would have missed three affected Pompe patients in our study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Assuming all four patients were affected, a frequency of 1:2,570 can be derived. In our study, we found similar mean enzyme activity and standard deviation in whole sample cohort as was found in the Austrian study (Dajnoki et al 2008). However, applying a cutoff value of 2 mmol/l/h would have missed three affected Pompe patients in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Our frequency for Pompe of 1:4,447 at best to 1:20,012 is higher compared to the Taiwanese population. In an anonymous Austrian pilot study for NBS of Pompe disease only 4 (0.039%) of 10,279 patients would have been recalled for retesting using a cutoff of 2 mmol/l/h (Dajnoki et al 2008). Assuming all four patients were affected, a frequency of 1:2,570 can be derived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this result, the recall rate would be 0.07%. Although this number remains to be confirmed by larger studies, it is comparable to the results obtained in studies for other lysosomal storage disorders: Pompe disease (0.039%) (Dajnoki et al 2008) and Krabbe disease (0.06%) (Orsini et al 2009). A higher recall rate (0.82%) was reported by Chien et al for Pompe NBS in Taiwan, but this likely results from a common a-glucosidase variant with low enzyme activity present in the Asian population (Chien et al 2008).…”
Section: Resultssupporting
confidence: 83%
“…Early intervention requires identification of patients at a very early age, before clinical features have become evident, i.e., by newborn screening (NBS) (Marsden and Levy 2010;Zhou et al 2011). NBS has been reported for a number of lysosomal storage disorders including Pompe disease (Chien et al 2008;Dajnoki et al 2008), Fabry disease (Dajnoki et al 2010), and Krabbe disease (Orsini et al 2009), but not for MPS II. Enzymatic assays for measuring the IDS activity in dried blood spots have been described in fluorometric (Oemardien et al 2011;Tolun et al 2012) and in tandem mass spectrometric (Wolfe et al 2011) platforms.…”
Section: Introductionmentioning
confidence: 99%